El debate en torno a la regulación de la igualdad de género en la familia - Gómez, Victoria (Política y Sociedad, 2008)
Family encapsulates some of the most prominent dimensions of gender equality since it is a main field of sharing life. The purpose of this paper is to briefly present some of these relevant questions in the context of the Spanish society at present. With a backdrop of a very rapid social change, this paper focuses on innovative new laws and consequent debates, paying attention to: (a) the limits of conciliation of employment and family life and the specific problems which Spanish women are facing nowadays, (b) equality after divorce, (c) new governmental measures against gender violence and subsequent criticism by feminists in favour of less punitive and more constructive rules, and finally (d) how homosexual marriage potentially comprises new theoretical ways of looking at gender equality.